Role of Breastfeeding and Onset of Atopic Dermatitis in Children Patient: a Cross Sectional Study - Arridha Hutami Putri; Sri Wahyuni Purnama; Irma Damayanti Roesyanto (Buletin Farmatera, 2020)
Abstract: Atopic dermatitis (AD) is a multifactorial disease belongs to the "burden disease" in childhood. It needs to be prevented to reach their optimal growth. Exclusive breastfeeding given during the first six months of life provides nutritional benefits and is thought to protect children from allergic or infectious diseases, such as AD. This study aims to determine the relationship between breastfeeding and onset of atopic dermatitis. This was an observational analytic study using cross-sectional method. Samples were taken consecutively at the Dermatovenereology Polyclinic of referral hospital and Puskesmas in Medan. This study included all pediatric patients aged 6 months to <18 years diagnosed with AD and were interviewed with informed consent. Children who didn’t get breastmilk were excluded. There result was a significant relationship between breastfeeding (exclusively to partially) and AD onset. There was no relationship between breastfeeding (exclusively to prelacteally) and AD onset. Polyunsaturated fatty acids, sIgA, and TGF-β2 in the breast milk of mothers with atopy is lower than mothers without atopy. Breastfeeding exclusively has a protective effect on AD. Further research is needed to analyzes various factors by comparing genetic predisposition.